La imatge triomfal de sant Miquel i la propaganda del poder en la cultura festiva. Història de les festes d’acció de gràcies celebrades a València el 1711 per les victòries felipistes a Brihuega i Villaviciosa durant la Guerra de Successió. - TORRES, ENRIC OLIVARES (Scripta, 2021)
The article analyzes the symbolic connection established through the festive spectacle between the image of the prince of the celestial militia, Saint Miquel, and that of King Philip V. The purpose of this union through literature, image and feast had as its main objective the strengthening of the privileged position of the monarch as sent from God while legitimizing, through his visuality and before his vassals, the absolute power of a monarchy that had to contend on the battlefield. On the other hand, the celebration of a thanksgiving party for the victories of Brihuega and Villaviciosa in 1711 was the ideal setting for the exhibition of sincere displays of loyalty and loyalty to the monarch by the city of Valencia. The Valencian celebration was framed in the context of a War of Succession that was about to be resolved in favor of Bourbon.